2020
DOI: 10.31234/osf.io/jubw5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do preferences for words and actions influence word-object and action-object learning in early childhood?

Abstract: Children live in a multimodal world: For example, communication with young children not only includes information from the auditory linguistic modality in the form of speech but also from the visual modality in the form of actions that caregivers use in the interaction with children. Dynamic systems approaches suggest that multimodal input can help children to learn from the environment while also allowing the child to shape their own learning experience through selective attention. This selective attention mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Thus, children as a group at this age may not display learning of either word-object or action-object associations. Later on, with increased language proficiency, as Eiteljoerge et al (2020) find, children between 2 and 3 years of age then reliably learn word-object associations in the context of the task tested in the current study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, children as a group at this age may not display learning of either word-object or action-object associations. Later on, with increased language proficiency, as Eiteljoerge et al (2020) find, children between 2 and 3 years of age then reliably learn word-object associations in the context of the task tested in the current study.…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, Barnhart et al (2018) suggested that this period may be associated with dynamically changing attention to different kinds of input, potentially at the individual level (c.f., Barnhart et al, 2018;Robinson & Sloutsky, 2004). In other words, it could be that some children attended more to actions at this age, while others might attend more to the language cues (Eiteljoerge et al, 2020), leading to some of them learning the actionobject associations and others learning the word-object associations. Thus, children as a group at this age may not display learning of either word-object or action-object associations.…”
Section: Discussionmentioning
confidence: 99%